UNIQUE APPLICATION OF SALES-ORIENTATION CUSTOMER-ORIENTATION (SOCO) SCALE AS A BEHAVIORAL ASSESSMENT TOOL TO PREDICT FUTURE ORIENTATION OF STUDENTS: A STUDY. Issue 3 (3rd July 2022) - Kushwaha, Tarun; Loya, Arpit; Jain, Prayatna; Kukrety, Deepti Bajpai
ABSTRACT: Sales management students carry certain misconceptions about sales jobs, which often create confusion in their minds about the nature of the sales job- should they be customer-oriented or sales-oriented? To excel in the initial years of their careers as effective salespersons, students might emphasize s ales-orientation or target achievement over customer-orientation. This might force them to choose manipulative practices in their professional lives. The orientation also depends upon the gender and prior sales experience of the students. Thus, if the instructors could assess the students' orientation, i.e., sales-orientation or customer-orientation, which they would practice during the job in advance, they could mentor them with proper inputs. The present study is an attempt to predict such orientations of the students by using a modified version of the SOCO scale. The findings suggest that gender and prior sales experience play a significant role in predicting the students' orientation in some cases.